Dying in cyberworld: violent video games extinguished children’s death concept and attitude - Hon, Kai Yee; Fok, Chee Kin; Chow, Ying Hui; Tan, Ren Jie; Dalton Julious Peter (Southeast Asia Psycholog, 2019)
Death is often a taboo topic in society, especially among the Chinese community. Most of the violent video games spread immoral values of life and death. Hence deformed death concept and death attitude are easily moulded in children particularly without proper supervision from parents. The misconception of death concept and death attitude can manipulate primary school children’s attitudes towards death which gradually might lead children to harm themselves or others. This study is aimed at identifying the relationship between violent video games and children’s death concept and death attitude (Fear of death, Death avoidance, Approach Acceptance, Escape Acceptance). The differences between the level of exposure to violent video games towards children’s death concept and death attitude are also carried out in this study. A total of 397 data was collected from Malaysian Chinese schoolchildren between 10 to 12 years of age by using the purposive sampling method. Instruments used in this study consist of demographic information, Death Attitude Media Violence Exposure. The study showed that a high level of exposure towards violent video games had a significant negative correlation with death concept and fear of death, whilst significantly positive correlation with escape acceptance. The result of the independent samples t-test showed that children with high exposure to violent video games had lower death concept and fear of death and a higher level of escape acceptance. Further research is needed to explore the death concept and attitude among children as technology has become an inseparable part of human beings in the 4th Industrial Revolution